The investigation of prevalence of Haemophilus influenzae type b in 3-6 years old children in day nurseries. - Cakmak, Burcak Tunc; Ardic, Nurittin; Demirpek, Ugur; Ozyurt, Mustafa; Haznedaroglu, TunOer; Sezen, Yavuz (Aves, 2005)
H. influenzae carriage is common seen in places such as day care center and school. In this study, the prevalence of H. influenzae type b was investigated in Anatolian side of Istanbul. Nasopharyngeal swab samples were obtained and transported to laboratory in a short time. The samples were cultivated on horse blood VBC chocolate agar medium at 37 degrees C under 5-10% CO2 for 24-48 hours. The colonies were evaluated by macroscopically and microscopically. Haemophilus-like colonies were subcultured on chocolate agar medium. The strains that need to X and V factors, catalase and oxidase-positive, no growing on sheep blood agar medium but growing on chocolate agar medium were evaluated as H. influenzae. Comparing with polivalent (type a, b, c, d, e, and f) and that Haemophilus influenzae tip b antisera by lam agglutination, these strains were typed. H. influenzae was isolated from 111 (22.2%) out of 500 children (242 girls and 258 boys) between 3-6 years old in the day care centers. Of these 111 isolates, 64 (58%) were determined as serotype b. The average carriage rate of H. influenzae tip b was determined as 12.8% (64 of 500). In conclusion, H. influenzae tip b infections should take into consideration as risk factor in day care center children.
Keywords: Haemophilus influenzae type b; day care center; prevalence